The relation between domestic violence and professional, contact sports: it's complicated - Sachs Swiderski, Nicole M. (Violence and victims, 2024)
Learning theories provide explanations for domestic violence; they can also aid in our understanding of the relation between contact sports and domestic violence. Notably, language used during sporting events and athletes’ behaviors being rewarded both on and off the field can influence the behaviors of viewers. Adubato (2016) found a statistically significant relation between an increase in domestic violence arrests and the kick-off times of Philadelphia Eagles football games. Here, we replicate and extend this work to Chicago and Boston. We examine quantitative, hourly data from the Chicago and Boston Police Departments and compare mean domestic violence arrests in an 8-hour period from the average Bears’ and Patriots’ (football) kick-off times, respectively, to the same time period on non-football Sundays, major holidays, and days of rival Blackhawks’ and Bruins’ (hockey) games, respectively. Results show a significant difference in average domestic violence arrests between hockey games and non-football Sundays in Chicago only. This work highlights the importance of context in examining domestic violence nationally and has implications for domestic violence policies in professional sports’ organizations.